2020
DOI: 10.7150/ijbs.42677
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-4 deficiency effectively protects the brain and neurological function in rodent after acute Hemorrhagic Stroke

Abstract: This study tested the hypothesis that abrogated dipeptidyl peptidase-4 (DPP4) activity played a crucial role on reducing stroke volume and preserving neurological function in rodent after acute hemorrhagic stroke (AHS). Animals (n=6/each group) were categorized into group 1 (sham-control of F344 rat), group 2 (sham-control of DPP4-deficiency rat), group 3 [AHS by right cerebral injection of autologous blood (100 µL) in F344 rat], group 4 (AHS + sitagliptin/600 mg/kg 3 h prior to and at 3 h then once per day af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…36 DPP4 deficiency effectively protects the brain and neurological function in rodent after ICH. 37 MK3102 is a potent DPP4 inhibitor. The expression of DPP4 was prominently reduced by MK3102 in ICH mice.…”
Section: Discussionmentioning
confidence: 99%
“…36 DPP4 deficiency effectively protects the brain and neurological function in rodent after ICH. 37 MK3102 is a potent DPP4 inhibitor. The expression of DPP4 was prominently reduced by MK3102 in ICH mice.…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptidyl peptidase-4 (DPP4), also known as CD26, is a widely expressed serine membrane-anchored peptidase that exists on the surface of various types of cell (7). Its expression level varies from cell to cell (8,9). In different organs and tissues (such as lung, muscle and heart), DPP4 activity is associated with its presence in the microvasculature (10).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we have demonstrated that individuals with angiodysplasia showed higher sCD26 and soluble DPP4 levels [ 49 ]. The presence in endothelial cells (also rich in CD26 [ 20 ]) of PAR-2, enhances angiogenesis on one hand [ 55 , 56 ] (CCL2 expression is also induced by soluble DPP4 [ 25 ]), and the well-known role of DPP4 activity in degrading pro-angiogenic chemokines, on the other [ 57 , 58 , 59 ], is a further unresolved issue probably with profound impacts in cancer treatment [ 24 ].…”
mentioning
confidence: 99%